Role of clec9A+ CD8+DCs in controlling malaria infection - Ang, Wei Ling (2015)
Dendritic cells (DCs) are the major antigen presenting cells (APCs) involved in orchestrating appropriate host immune response against Plasmodium parasites since they form a large phagocyte network inside the red pulp of spleen - a major site for control of blood-borne diseases such as malaria. Splenic DCs represent remarkable phenotypic heterogeneity but their functional role in containing the Plasmodium infection remains unknown. Since conventional DCs (cDCs) present Plasmodium antigens to prime T cell responses during the acute phase of malarial infection, we hypothesized that CD8+ cDCs could play a role in controlling acute and chronic P. chabaudi infection by regulating T cell-mediated and antibody-mediated responses. Hence, we exploited Clec9A-DTR transgenic mice, which allow specific ablation of CD8+Clec9A+DC subset upon diptheria toxin administration. As compared to wild-type, Clec9A-DTR mice show significantly lower IFN-ɣ production in acute phase and higher parasitemia in chronic phase. Phenotype rescue via injection of CpG-induced IFN-ɣ reiterates the importance of IFN-ɣ in controlling the infection as parasitemia levels were reduced. Moreover, sera transfer from infected WT and Clec9A-DTR mice into naive mice infected with P. chabaudi showed that Clec9A+ CD8+ DCs initiate better protection against P. chabaudi infection through the polarization of IgG1 and IgG2c.